Implications of Microscopic Satellites of the Primary and Extracapsular Lymph Node Spread in Patients With High-Risk Melanoma: Pathologic Corollary of Eastern Cooperative Oncology Group Trial E1690 - Rao, U.N.M.; Ibrahim, J.; Flaherty, L.E.; Richards, J.; Kirkwood, J.M. (Journal of clinical oncology, 2002)
PURPOSE: To correlate the presence of extracapsular spread (ECS) of regional nodal metastases, and micrometastasis near the primary tumor, with disease outcome in the intergroup study E1690 in relation to the impact of recombinant interferon-alfa (rIFNα)-2b. PATIENTS AND METHODS: E1690 included 642 patients with American Joint Committee on Cancer stage IIB or III cutaneous melanoma. Patients were randomized into high- and low-dose rIFNα-2b treatment arms and an observation arm. Pathologic slides were reviewed for selected parameters from at least half of the subjects in all three arms. Evaluation of the primary tumor included notations regarding ulceration, mitotic activity, thickness, microscopic satellites (MS), and nodal ECS on a standardized pathology form. These data were collated in relation to relapse-free survival (RFS) and overall survival (OS) at 50 months’ follow-up and studied using Cox regression analysis. RESULTS: Ulceration, mitotic activity, thickness, and size of tumor-bearing lymph nodes did not show a statistically significant correlation with either OS or RFS across all treatment arms. The presence of MS was correlated with RFS (P = .0008) and OS (P = .05). ECS correlated with RFS (hazard ratio = 1.44, P = .032) but not OS (P = .11). CONCLUSION: The presence of MS (in 6% [18 of 308 patients]) had a significant adverse impact on both RFS (P = .0008) and OS (P = .053). Ulceration, mitotic activity, thickness, and number of positive lymph nodes had no significant effect on OS in this subset study (univariate or multivariate Cox analysis). The presence of ECS in lymph nodes had a significant adverse effect on RFS (P = .032) but not on OS.